Results based management in fisheries: Delegating responsibility to resource users. (January 2015) - Nolde Nielsen, Kåre; Holm, Petter; Aschan, Michaela
Abstract: While the notion of results based management has been devoted recent attention in the context of reforming European fisheries management, it remains unclear what it entails. A conceptual model of results based management in fisheries is proposed as a way for public authorities to delegate specific management and documentation responsibilities to resource users. The model comprises three defining features: (1) That authorities define measurable objectives for the utilization of fisheries resources; (2) that resource users are made responsible for achieving these objectives and for (3) providing documentation that allows for an audit of the extent to which they are met. Selected cases are used to illustrate these features. Rationales and prospects of introducing results based management as an alternative in a European fisheries management context are discussed, giving consideration to how it may be pursued under the reformed common fisheries policy. Highlights: In results based management (RBM), responsibility for achieving defined objectives is delegated to resource users. RBM integrates rationales of state centred, participatory and market based governance. RBM requires that authorities accept and motivate delegation of defined responsibilities for management and documentation, and that resource users develop organizational capacity and foster leadership. Elements of RBM are currently emerging within the common fisheries policy area but lessons can be learned from more comprehensive examples in New Zealand.